The performance and limitations of PCA3, TMPRSS2:ERG, HOXC6 and DLX1 urinary markers combined in the improvement of prostate cancer diagnostics - Mytsyk, Yulian; Nakonechnyi, Yosyf; Dosenko, Victor; Kowal, Paweł; Pietrus, Michał; Gazdikova, Katarina; Labudova, Monika; Caprnda, Martin; Prosecky, Robert; Dragasek, Jozef; Kruzliak, Peter; Dats, Roman (Clinical biochemistry, 2023)
BACKGROUND: Prostate cancer (PCa) is the second most commonly diagnosed cancer in men. To date, the role of the combined application of long non-coding RNAs (PCA3, DLX1, HOXC6, TMPRSS2:ERG) for obtaining the most accurate method of detection of PCa has not yet been comprehensively investigated. METHODS: In total 240 persons were included in the retrospective study. Among them were 150 patients with confirmed PCa, 30 patients with benign prostatic hyperplasia, 30 patients with active chronic prostatitis and 30 healthy volunteers. In all patients, the urine samples were collected prior to biopsy or treatment. Polymerase chain reaction with reverse transcription was performed to detect the expression level of PCA3, HOXC6, DLX1 and the presence of the TMPRSS2:ERG transcript. RESULTS: PCA3 was detected in urine samples in all cases. Using a PCA3 score of 56 allowed the differentiation between PCa and all other cases with a sensitivity of 61% and specificity of 96% (p < 0.001) while a PCA3 score threshold value of 50 resulted in a differentiation between clinically significant PCa (ISUP grades 2-5) and all other cases with a sensitivity of 93% and specificity of 93% (p < 0.001). The TMPRSS2:ERG expression in urine was detected exclusively in the group of patients with PCa and only in 16% of all cases. CONCLUSIONS: PCA3 score detected in urine demonstrated moderate sensitivity and good specificity in differentiation between PCa and non-PCa and high sensitivity and specificity in differentiation between clinically significant PCa and non-PCa.
Keywords: PCA3; Urinary marker; Male; HOXC6; retrospektivní studie; Prostate; antigeny nádorové; Diagnostics; TMPRSS2:ERG; Prostatic Neoplasms; mužské pohlaví; prostata; fúzní onkogenní proteiny; transkripční regulátor ERG; prostatický specifický antigen; Oncogene Proteins, Fusion; lidé; RNA; Serine Endopeptidases; Humans; Prostate cancer; Transcriptional Regulator ERG; serinové endopeptidasy; nádory prostaty; DLX1; Antigens, Neoplasm; Retrospective Studies; Homeodomain Proteins; Biomarkers, Tumor; homeodoménové proteiny; nádorové biomarkery; Prostate-Specific Antigen